The histopathology of the eye of big head carp, Aristichthys noblis (Richardson), infested with Lernaea piscinae Harding, 1950 - Shariff, M. (Wiley, 1981)
The histopathological changes in the eye due to the penetration and growth of the parasite, Lernaea piscinae, in the host tissue of big head carp is described. Distinct pathological changes were hyperplasia of the corneal epithelium, severe inflammatory response mainly around the anchor of the parasite, in the anterior chamber, the corneal stroma and the vitreous body and detachment of the vitreous and retinal layers. Rupture of the lens capsule and fibrous tissue response around the process of the anchor structure of the parasite were also observed. The development of an immune response to the parasite within the body of the host is thought to have led to the infection of the cornea, an avascular site.